Factors influencing international students' decision to study in Universiti Utara Malaysia - Nur Fatin, Md Khalid (2015)
Nowadays, higher education is becoming increasingly globalized and internationalized. Malaysia today aspires to be a regional hub of higher education where internationalization is believed to be the best empowerment approach to throw the country’s higher education to world class. The number of international students studying in Malaysian institution of higher education is continuously growing. International students contribute their own success, campus diversity, campus internationalization and also economic of Malaysia. Universiti Utara Malaysia (UUM) meets the challenges of internationalization by offering learning opportunities to international students. The purpose of this study is to identify the factors that influencing international student’s decision to study in UUM. However, this study will focus only on all the international students in UUM, total 2608 international students in different education level and from different countries. This study is a quantitative research. The questionnaires were distributed to the respondent. A total of 289 international students at UUM provide feedback via the questionnaires form. Technique of regression analysis and Pearson Correlation in SPSS is used to identify the relationship and test the hypothesis. The findings of this study indicate that there is a significant and positive relationship between university reputation, pricing and promotion/advertising with decision of international student’s choosing UUM to further study.